Acute Myeloid Leukemia with Platelet-Derived Growth Factor Receptor β (PDGFRβ) Rearrangement Successfully Treated with Intensive Chemotherapy in Combination Withimatinib- A Case Report - Witkowska, Ewelina; Jerzmanowska, Katarzyna; Wawrzyniak, Ewa; Robak, Marta; Wierzbowska, Agnieszka; Pluta, Agnieszka (Archives of Clinical and Medical Case Reports, 2021)
Acute myeloid leukemia (AML) is a heterogeneous clonal stem cell malignancy. Several subgroups of AML have been identified based on multiple genomic and proteomic aberrations; these demonstrate different clinical features, response to treatment and prognosis. Rearrangements in the platelet-derived growth factor receptor β (PDGFRβ) gene result in greater constitutive enzymatic activity (tyrosine kinase) and deregulation of haematopoiesis, similarly to BCR-ABL1 in chronic myeloidleukemia (CML). PDGFRβ gene rearrangements are infrequent entities, which are mostly diagnosed in patients presenting with atypical CML, chronic myelomonocytic leukemia (CMML), myelodysplastic/myeloproliferative disorders (MDS/MPN) or juvenile myelomonocytic leukemia (JMML). PDGFRβ-positive AML is extremely rare, accounting for well below 1% of all cases. In this article, we present the case of a 31-year-old woman with AML and abnormal karyotype with PDGFRβ rearrangement, who was treated with intensive chemotherapy combined with low-dose imatinib. Complete remission (CR) was achieved and imatinib was used as maintenance treatment. The patient remains in CR with disease-free survival (DFS) of 41 months.